2023
DOI: 10.1007/s00192-023-05527-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of a prospective randomized trial comparing tension-free vaginal tape versus transobturator tape in stress urinary incontinence

Abstract: Introduction and hypothesis This study was aimed at investigating the long-term effectiveness of minimally invasive mid-urethral sling (MUS) surgery and at comparing the outcomes between retropubic (tension-free vaginal tape, TVT) and transobturator tape (TOT) methods in the treatment of stress urinary incontinence (SUI) and mixed urinary incontinence (MUI) with a predominant stress component in a long-term follow-up of a randomized controlled trial. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…This lack of agreement leads to contradictory conclusions in various studies, with some authors favoring one technique over the other on the basis of their findings [5,[47][48][49]. One consistent and universal finding reproduced across these studies is that both techniques have shown clear evidence of safety and satisfactory efficacy, not just in the short term but also over medium and long-term periods [50,51]. In addition to their proven safety, each technique has a specific complication profile, enabling physicians to effectively anticipate and document any potential intraoperative and postoperative issues.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of agreement leads to contradictory conclusions in various studies, with some authors favoring one technique over the other on the basis of their findings [5,[47][48][49]. One consistent and universal finding reproduced across these studies is that both techniques have shown clear evidence of safety and satisfactory efficacy, not just in the short term but also over medium and long-term periods [50,51]. In addition to their proven safety, each technique has a specific complication profile, enabling physicians to effectively anticipate and document any potential intraoperative and postoperative issues.…”
Section: Discussionmentioning
confidence: 99%